2023
DOI: 10.1186/s12889-023-16462-5
|View full text |Cite
|
Sign up to set email alerts
|

Health disparities in COVID-19: immune and vascular changes are linked to disease severity and persist in a high-risk population in Riverside County, California

Kristina V. Bergersen,
Kathy Pham,
Jiang Li
et al.

Abstract: Background Health disparities in underserved communities, such as inadequate healthcare access, impact COVID-19 disease outcomes. These disparities are evident in Hispanic populations nationwide, with disproportionately high infection and mortality rates. Furthermore, infected individuals can develop long COVID with sustained impacts on quality of life. The goal of this study was to identify immune and endothelial factors that are associated with COVID-19 outcomes in Riverside County, a high-ri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The markers that are used to assess the glomerular filtration rate and overall function of the kidneys are creatinine and neutrophil gelatinase-associated lipocalin (NGAL) [15]. Development of AKI in the course of COVID-19 has been confirmed in many studies; however, researchers argue that serum creatinine and NGAL measurements are as useful as urine measurements of these markers [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The markers that are used to assess the glomerular filtration rate and overall function of the kidneys are creatinine and neutrophil gelatinase-associated lipocalin (NGAL) [15]. Development of AKI in the course of COVID-19 has been confirmed in many studies; however, researchers argue that serum creatinine and NGAL measurements are as useful as urine measurements of these markers [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In severe COVID-19, similar to sepsis, there is a trend of dropping platelet counts, particularly in patients with severe disease [17]. A metaanalysis of 7,613 COVID-19 patients revealed that patients with severe disease had a lower platelet count than those with non-severe disease.…”
Section: Introductionmentioning
confidence: 99%
“…In severe COVID-19, similar to sepsis, there is a trend of decreased platelet counts, particularly in patients with severe disease [ 17 ]. A meta-analysis of 7613 COVID-19 patients revealed that patients with severe disease had a lower platelet count than those with non-severe disease.…”
Section: Introductionmentioning
confidence: 99%